PENGARUH AUDIT FEE, AUDIT TENURE, DAN ROTASI AUDIT TERHADAP KUALITAS AUDIT (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2022) - Christina Sososutiksno; Putri Sucita Deeng (JURNAL ILMIAH EDUNOMIKA, 2023)
The aim of this research is to determine the effect of audit fees, audit tenure and audit rotation on audit quality. The sample used in this research is a manufacturing company listed on the Indonesia Stock Exchange in 2019-2022. Data were analyzed using SPSS. The results of this study indicate that audit fees have no effect on audit quality. This can occur because the determination of audit fees has been officially regulated by IAPI, so that it does not directly affect audit quality. Audit tenure affects audit quality, indicating that the longer the tenure, the more competent the auditor will be because the auditor understands internal control, accounting information systems, and company-specific risks. Audit rotation has no effect on audit quality, indicating that auditors who have a professional attitude will act independently in carrying out audits so that it is good to do audit rotation or not if an auditor upholds independence will not be affected by things that can reduce audit quality.